Fire performance of ductile fiber reinforced cementitious composites - Liu, Jincheng (2018)
Ductile fiber reinforced cementitious composite (DFRCC), emerged in early 1990s, has been proven to be an excellent building material in terms of structural performance at ambient temperature. Many studies have demonstrated that DFRCC outperforms conventional concrete in terms of seismic performance, impact resistance and durability due to its high tensile ductility and multiple fine cracking behaviors. However, behavior of DFRCC at elevated temperatures remains questionable so far. As fire accidents occur frequently in buildings, there is an urgent need to improve and evaluate fire performance of DFRCC. This thesis focuses mainly on two topics: (a) improve and study mechanical performance of fire-damaged DFRCC (b) re-examine fire-induced concrete spalling mechanism and assess thermal spalling risk of DFRCC. An experimental program was designed to optimize post-fire responses of DFRCC. The optimized DFRCC mix was then subjected to fire resistance testing, which covered two aspects, i.e., residual mechanical properties and thermal spalling resistance. The optimized DFRCC were observed to perform better than normal concrete in these two aspects. Fire-induced spalling is perhaps the least understood of the major issues plaguing concrete in fire. Many studies have attempted to better understand the underlying mechanisms behind fire-induced spalling; however, several controversies still exist. A unified fire-induced concrete spalling theory was advanced in this thesis, which classifies fire-induced spalling into three types based on their distinct spalling mechanisms. They are thermo-hygral, thermal-mechanical, and thermal-chemical spalling, respectively. Hot permeability test and microstructural analysis techniques were used to study the mechanism of PVA fibers in DFRCC to combating thermo-hygral spalling. A numerical model with reasonable accuracy was also proposed to assess thermo-hygral spalling risk of concrete.